Characterizations of local A∞ weights and applications to local singular integrals - Campos, Federico Augusto (2023)
In a general geometric setting, we prove different characterizations of a local version of Muckenhoupt A∞ weights. As an application, we obtain conclusions about the relationship between this class and the one-weight boundedness of local singular integrals from L∞ to BMO.